Effect of health belief model-based education on infection control standard precautions in prehospital emergency staff: A clinical trial study - Roya Amini; Mahnaz Mohamadkhani; Masoud Khodaveisi; Manoochehr Karami (Wolters Kluwer Medknow Publications, 2021)
Background: Standard precautions are a basic strategy to prevent occupational exposure in prehospital emergency staff. The Health Belief Model (HBM)-based education can be used to promote and educate health behavior. The aim of this study was to investigate the effect of the HBM-based education on infection control standard precautions in prehospital emergency technicians. Materials and Methods: This clinical trial study was conducted on 84 prehospital emergency staff of Hamadan who were randomly assigned to two groups: Experimental (n: 42) and control (n: 42) using a cluster method. The data were collected by a researcher-developed questionnaire. Before education, the questionnaires were completed by both groups, and then three educational sessions were held for the experimental group within one month. Two months after the intervention, the two groups completed the questionnaire and the data were analyzed by SPSS 21 software. Results: Before education, there was no significant difference in the mean scores on HBM constructs and performance between the two groups (p > 0.05). The results of the Analysis of Covariance (ANCOVA) after educational intervention showed there was a significant difference in the mean scores of all constructs and performance between the two groups (p < 0.05). Conclusions: HBM-based educational intervention could affect the scores of the model's constructs and improve the use of standard precautions in emergency medical technicians. In-service training is recommended to be developed for the staff based on HBM.